Effect of Hydroponically Grown Forages on Growth Performance of Rabbit - Shah, Manoj Kumar; Magar, Milan Thapa; Shah, Shatrughan (International Journal of Applied Sciences and Biotechnology, 2023)
An experiment was carried out on weaned rabbits at Swine and Avian Research Program, Khumaltar from 11 June 2020 to July 29, 2020 after adjustment period of seven days. The objective to evaluate the effect of hydroponically grown forages on growth performance of rabbit. The experiment was laid out in completely randomized design with three treatments viz. control without inclusion of hydroponic forage (T1), combination of pea and wheat hydroponic forage (T2), concentrate mixture with pea hydroponic forage (T3) and concentrate mixture with wheat hydroponic forage (T4) in rabbit feeding diet. A total of 60 rabbits each treatment containing 5 rabbits kept for 8th weeks’ period. The data on feed intake was recorded daily and body weight was measure in weekly basis. Combination of pea and wheat hydroponic forage treatment showed the significant results on feed intake, weight gain and feed conversion ratio(FCR). The experiment revealed that the highest forage hydroponic forage intake (177.48 g) and weight gain (158.67g) was observed in T2 (combination of pea and wheat in hydroponics system) and lowest in T1 (46.67g). The highest FCR was found in T1 (3.75) and lowest in T2 (2.28). The results of this study showed that growth performance of rabbits on combination of pea and wheat hydroponically grown forage feeding practices at intensive system found better than without hydroponically grown forage feeding practices. Further study should be carried out to precise the appropriate hydroponic forage recommending this practices to the rabbit growers.